Usulan Rute Distribusi Menggunakan Algoritma Sweep dan 1-0 Insertion Intra Route di CV. XYZ - Riyadi, Vina Fahrezi; Imran, Arif; Rizkiani, Firda Nur (e-Proceeding FTI, 2024)
This distribution activity is one of the important achievements for manufacturing companies in order to operate efficiently and effectively. However, CV. XYZ carries out its distribution based solely on estimates without calculating the distance traveled, the capacity of the conveyance, or the travel time. The company handles deliveries with varying demands among its customers, and each vehicle has a maximum capacity limitation. This problem is known as the Capacitated Vehicle Routing Problem (CVRP). One way to solve the problem in the company is to use the Sweep Algorithm and 1-0 Insertion Intra Route. Based on the results of data processing, the proposed distribution route to minimize mileage uses the 1-0 Insertion Intra Route Algorithm, resulting in a total distance of 248.6 km with a travel time of 14.380 hours. This approach achieves a distance savings of 22.09% compared to the actual route. Keywords: Distribution Routing, Sweep Algorithm, Insertion, VRP. Kegiatan distribusi ini menjadi salah satu pencapaian penting bagi perusahaan manufaktur agar dapat beroperasi dengan efisien dan efektif. CV. XYZ dalam melakukan pendistribusiannya hanya berdasarkan perkiraan saja tanpa perhitungan jarak tempuh, kapasitas alat angkut atau waktu tempuhnya. Perusahaan melakukan pengiriman dengan permintaan yang bervariasi di antara pelanggannya dan setiap kendaraan memiliki batasan kapasitas maksimum. Permasalahan tersebut dikenal sebagai Capacitated Vehicle Routing Problem (CVRP). Salah satu untuk menyelesaikan permasalahan pada perusahaan tersebut menggunakan Algoritma Sweep dan 1-0 Insertion Intra Route. Berdasarkan hasil pengolahan data, usulan rute distribusi untuk mendapatkan jarak tempuh minimum menggunakan Algoritma 1-0 Insertion Intra Route yang menghasilkan total jarak 248,6 km dengan waktu 14,380 jam. Penghematan jarak terhadap rute aktual diperoleh sebesar 22,09%. Kata kunci: Rute Distribusi, Algoritma Sweep, Insertion, VRP.